Excellence criteria of services supply chain in management consulting institutes of Iran. Issue 1 (5th March 2018) - Balouei Jamkhaneh, Hadi; Safaei Ghadikolaei, Abdol Hamid; Madhoushi, Mehrdad; Yahyazadehfar, Mahmood
Abstract : Purpose: The purpose of this study was to identify the excellence criteria of services supply chain (SSC) in Iran and the relationship between them and the importance of each criterion. Design/methodology/approach: In this paper, after reviewing the principles and evaluating models of SSCs, using the fuzzy Delphi method, the criteria for excellence in the supply chain processes were identified. Then, the relationships between these criteria and their significance were evaluated using decision-making trial and evaluation laboratory (DEMATEL) and DEMATEL-based analytic network process methods. Findings: The results show that 19 evaluation criteria have been identified in Iran in accordance with the SSC process. These criteria were classified according to their nature and based on the Deming Excellence Model and ISO 9004 standards in four areas: Plan, Do, Check and Act. In addition, the Act dimension with the weight of 0.275 has the highest importance and the Plan dimension with the weight of 0.219 has the lowest importance. Practical implications: This study attempted to identify appropriate criteria for SSC processes in management consulting firms by examining supply chain assessment models to provide the managers with the right understanding of this industry for performance assessment so that they have a better knowledge of supply chain processes. Originality/value: The results will be useful for managers to understand the SSC and the ways of SSC excellence in a service organization. This research is a first step for evaluating SSC performance of management consultancy institutes. In fact, after the identification of SSC processes and evaluation criteria, designing a mechanism for the evaluation of the performance of SSCs can be a subject for future research.